The effect of Schisandra chinensis extracts on depression by noradrenergic, dopaminergic, GABAergic and glutamatergic systems in the forced swim test in mice. Issue 6 (26th May 2016) - Yan, Tingxu; Xu, Mengjie; Wu, Bo; Liao, Zhengzheng; Liu, Zhi; Zhao, Xu; Bi, Kaishun; Jia, Ying
Abstract : Schisandra chinensis (Turcz.) Baill., as a Chinese functional food, has been widely used in neurological disorders including insomnia and Alzheimer's disease. Abstract : Schisandra chinensis (Turcz.) Baill., as a Chinese functional food, has been widely used in neurological disorders including insomnia and Alzheimer's disease. The treatment of classical neuropsychiatric disorder depression is to be developed from Schisandra chinensis . The antidepressant-like effects of the Schisandra chinensis extracts (SCE), and their probable involvement in the serotonergic, noradrenergic, dopaminergic, GABAergic and glutamatergic systems were investigated by the forced swim test (FST). Acute administration of SCE (600 mg kg −1, i.g.), a combination of SCE (300 mg kg −1, i.g.) and reboxetine (a noradrenalin reuptake inhibitor, 2.5 mg kg −1, i.p.) or imipramine (a TCA, 2 mg kg −1, i.p.) reduced the immobility time in the FST. Pretreatment with N -(2-chloroethyl)- N -ethyl-2-bromobenzylamine hydrochloride (DSP-4, a selective noradrenergic neurotoxin, 50 mg kg −1, i.p., 4 days), haloperidol (a non-selective D2 receptor antagonist, 0.2 mg kg −1, i.p.), SCH 23390 (a selective D1 receptor antagonist, 0.03 mg kg −1, i.p.), bicuculline (a competitive GABA antagonist, 4 mg kg −1, i.p.) and N -methyl-d -aspartic acid (NMDA, an agonist at the glutamate site, 75 mg kg −1, i.p.) effectively reversed the antidepressant-like effect of SCE (600 mg kg −1, i.g.). However, p -chlorophenylalanine (pCPA, an inhibitor of 5-HT synthesis, 100 mg kg −1, i.p., 4 days, ) did not eliminate the reduced immobility time induced by SCE (600 mg kg −1, i.g.). Moreover, the treatments did not change the locomotor activity. Altogether, these results indicated that SCE produced antidepressant-like activity, which might be mediated by the modification of noradrenergic, dopaminergic, GABAergic and glutamatergic systems.